2018
DOI: 10.3390/v10100546
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Characterization of Orthopoxvirus (OPV) Abatino, a Zoonotic Virus Representing a Putative Novel Clade of Old World Orthopoxviruses

Abstract: Orthopoxviruses (OPVs) are diffused over the complete Eurasian continent, but previously described strains are mostly from northern Europe, and few infections have been reported from Italy. Here we present the extended genomic characterization of OPV Abatino, a novel OPV isolated in Italy from an infected Tonkean macaque, with zoonotic potential. Phylogenetic analysis based on 102 conserved OPV genes (core gene set) showed that OPV Abatino is most closely related to the Ectromelia virus species (ECTV), althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
15
0
2
Order By: Relevance
“…Comparative analysis of the full-length sequence of CPXV GerMygEK 938/17 showed the highest nucleotide sequence identity (99.2%) to a virus isolated from a cotton-top tamarin ( Saguinus oedipus ) in Germany 2010 (CPXV Ger2010MKY, GenBank accession number LT896721) [43] (Figure 2a). CPXV GerMygEK 938/17 and CPXV Ger2010MKY (CPXV MKY) sequences form a separate cluster provisionally named “CPXV-like 3” clade [16] in close proximity to the OPV isolate Abatino from Italy (MH816996) pairwise identity 93.8%, which was referred to as ECTV-like [55,56] and ECTV strains (pairwise identity ECTV strain Moscow 85.3%). Similarity plot analysis showed areas of high sequence variation between CPXV GerMygEK 938/17 and OPV Abatino (Figure 2b), while comparison to CPXV MKY indicated only small variations (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative analysis of the full-length sequence of CPXV GerMygEK 938/17 showed the highest nucleotide sequence identity (99.2%) to a virus isolated from a cotton-top tamarin ( Saguinus oedipus ) in Germany 2010 (CPXV Ger2010MKY, GenBank accession number LT896721) [43] (Figure 2a). CPXV GerMygEK 938/17 and CPXV Ger2010MKY (CPXV MKY) sequences form a separate cluster provisionally named “CPXV-like 3” clade [16] in close proximity to the OPV isolate Abatino from Italy (MH816996) pairwise identity 93.8%, which was referred to as ECTV-like [55,56] and ECTV strains (pairwise identity ECTV strain Moscow 85.3%). Similarity plot analysis showed areas of high sequence variation between CPXV GerMygEK 938/17 and OPV Abatino (Figure 2b), while comparison to CPXV MKY indicated only small variations (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…The closest branch to CPXV GerMygEK 938/17 and CPXV Ger2010MKY consists of OPV Abatino isolate from an Italian Tonkean macaque ( Macaca tonkeana ). This strain is very similar to another OPV-derived sequence from an Italian cat [55,56,63]. During the Italian macaque outbreak, trapped rodents were tested negative for OPV-reactive antibodies [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several novel poxviruses have been discovered after infecting humans and/or domestic animals [22,23,24,25,26,27,28,29,30,31], including three newly proposed OPXV species: two isolated in Europe and one isolated in North America. Orthopoxvirus Abatino (OPVA) was isolated in Italy during an outbreak in captive macaques in 2015 and from a fatal infection in a cat in 2017 [28,29,31]. Another novel proposed OPXV, Ahkmeta virus (AKMV), was identified in three humans in the country of Georgia in 2010 and 2013 [22,27].…”
Section: Introductionmentioning
confidence: 99%
“…There are currently three known species of New World or North American OPXVs: Raccoonpox virus ( RCNV ), Volepox virus ( VPXV ) and Skunkpox virus ( SKPV ) [32,35]. Newly described OPVA [29] and AKMV [27] cluster with Old World OPXVs in phylogenetic analyses, in agreement with their isolation in Europe, although AKMV is divergent [27]. The novel poxvirus isolated from Alaska in 2015 clustered with OPXVs, but formed a distinct clade, apart from Old World and New World OPXVs, based on preliminary analysis of nine conserved genes [30].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore suggested that the AKMVs examined here are different strains of the same virus species. A recent poxvirus phylogeny report showed CPXV-Ger2010MKY (LT896721) branches off earlier than all of the extant orthopoxviruses, at a position similar to that of Akhmeta viruses (14). This relationship was not reproduced in Fig.…”
Section: Resultsmentioning
confidence: 99%